Actinomyces Naeslundii and Aggregatibacter Aphrophilus Brain Abscess in an Adolescent - Croix, Michael; Schwarz, Christopher; Breuer, Ryan; Hassinger, Amanda B.; Chadha, Kunal; Hicar, Mark Daniel (Archives of Clinical and Medical Case Reports, 2019)
We report the case of a child with a brain abscess from which Actinomyces naeslundii and Aggregatibacter aphrophilus were isolated. The is the first case describing A. naeslundii causing a brain abscess. This case highlights the association of these two organisms which may affect antibiotic choice and therapy length.